First Report of Proton Beam Therapy in a Patient With a Left Ventricular Assist Device. Issue 5 (6th May 2021) - Schumer, Erin M.; Schettle, Sarah; Stulak, John M.; Rosenbaum, Andrew N.
Abstract : A 77 year old man previously implanted with a HeartMate II left ventricular assist device (LVAD) as destination therapy and an implantable cardioverter defibrillator presented with a left upper lobe squamous cell lung cancer. Oncology determined that proton beam therapy was indicated for treatment, and a multidisciplinary team of radiation physicists, radiation oncologists, and LVAD providers developed a protocol to proceed safely. He was successfully treated with combined proton beam radiation therapy and reduced dose chemotherapy. This case demonstrates feasibility and considerations of proton beam therapy for malignancy relevant to patients with implantable cardiac devices including LVADs.